EFFECT OF ATRAZINE AND MESOTRION HERBICIDES AND THEIR MIXTURES AGAINTS TUTON GRASS (ECHINOCHOLA COLONA) - JANUALIUS JANUALIUS (Jurnal Sains Pertanian Equator, 2020)
Weed is a plant that is detrimental to human interest. this study aims to evaluate the effect of atrazine and mesotrion herbicides and their mixtures on weed echinochola colona. the study was conducted at the experimental garden and pestiside Laboratory of the faculty of agriculture, Tanjungpura University, Pontianak in september - November 2019. The research was carried out using a randomized block design. the herbicide used is atrazine, mesotrion and its'mixture. Each herbicide treatment consisted of 5 dose levels, plus control, with 5 replications in each treatment. Weed poisoning intensity and weed dry weight data were observed. Probit analysis is used for SAS applications. Mesotrion herbicide with a dose of 0.63 1/ha, 1.25 1/ha and 2.5 1/hacan inhibit the growth of echinocholoa colona weeds, but cannot completely kill weeds.